A NEW METHOD OF UNIFIED PROCESSING OF THE INFORMATION, REFERRED IN THE FORM OF THE THREE-DIMENSIONAL ASSOCIATIVE-LOGICAL STRUCTURE FOR OPTIMIZATION OF THE MULTIROTOR UNMANED AVIATION SYSTEM - Kharchenko, Volodymyr; Nakhaba, Alexandr (Proceedings of National Aviation University (archive), 2017)
Purpose: This article presents a mathematical model and a new way of unified information processing. Methods: Three-dimensional associative-logical synthesis. Results: Obtained a new experimental data. Discussion: The present invention can be used in the following directions: 1) in epistemology, the basis for a more effective and purposeful scientific search in all branches of science; 2) in psychology and pedagogy - the basis for a more effective and universal thinking of man in almost all sections of science; 3) in electronics and computer science - the basis for the creation of artificial intelligence systems and high-quality systems for speech and images recognition, provided that are created the chips in which the storage elements are interconnected in three dimensions; 4) in the aerospace and robotics sectors - the possibility of developing a new, more advanced autopilot systems, capable of working according to the principles of the neural network of biological objects.